2008
DOI: 10.1017/s1368980008002322
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of usage and fatty acid composition of cooking fats in Bogotá, Colombia

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…It was decided to collect at least one 24 h recall and one dietary record, and whenever possible we collected more than 2 d. In the end, the number of dietary records and 24 h recalls varies from one to six with an average of three per child. Each food from the dietary records and 24 h recalls was coded according to guidelines from Monteiro et al and the nutrient composition of these foods was found using US Department of Agriculture food composition tables complemented with local food tables and chromatography analysis of fatty acids in cooking oils (8,9,16) . The three processed food categories are (i) unprocessed and minimally processed foods, (ii) processed culinary ingredients and (iii) processed and ultra-processed food products, according to the original classification of Monteiro et al (9) .…”
Section: Methodsmentioning
confidence: 99%
“…It was decided to collect at least one 24 h recall and one dietary record, and whenever possible we collected more than 2 d. In the end, the number of dietary records and 24 h recalls varies from one to six with an average of three per child. Each food from the dietary records and 24 h recalls was coded according to guidelines from Monteiro et al and the nutrient composition of these foods was found using US Department of Agriculture food composition tables complemented with local food tables and chromatography analysis of fatty acids in cooking oils (8,9,16) . The three processed food categories are (i) unprocessed and minimally processed foods, (ii) processed culinary ingredients and (iii) processed and ultra-processed food products, according to the original classification of Monteiro et al (9) .…”
Section: Methodsmentioning
confidence: 99%
“…A previous study that investigated the composition and usage of cooking fats in Bogotá, Colombia found that mixed vegetable oils (composed of soybean, corn, and palm oil) and sunflower oil were most commonly used in this population (29). Biochemical analyses revealed that the mixed vegetable oils used by those of lower socioeconomic status had the highest ALA content.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical analyses revealed that the mixed vegetable oils used by those of lower socioeconomic status had the highest ALA content. On the other hand, sunflower oil, which was preferred by the more affluent, contained negligible amounts of PUFAs and higher trans fat content (29). Because Colombia has one of the lowest intakes of marine fish worldwide (30), home-cooking oils represent the main source of dietary fatty acids in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…In South America, consumption of margarine has been recommended as a preferred option over butter to reduce the risk of cardiovascular disease [ 13 ]. Colombian margarines, in particular, have been described to have a lower trans -fatty acid content and higher levels of saturated fatty acids than the levels observed in margarines from other Latin American countries [ 14 ]. It might be possible that the lower content of trans -fatty acids makes margarine unlikely to have a detrimental effect on allergic symptoms in the children studied in Barranquilla.…”
Section: Discussionmentioning
confidence: 99%